Exploring the state of social entrepreneurship in Malaysia - Mohd Adnan, Raudah (2022)
Social entrepreneurship in Malaysia is relatively new and is still in the introduction stage. Some studies have shown it to be increasingly difficult to sustain due to limitations to access opportunities and resources. However, the introduction of Social Entrepreneurship Blueprint 2015 had triggered interests among entrepreneurs and provided more opportunities for them to explore the roles of social entrepreneurship sector. In the Malaysian perspective, a comprehensive framework of social entrepreneurship state needs to be developed as a catalyst for sustainable development. Therefore, this study aimed to explore the current landscape and the development of social entrepreneurship in Malaysia, and then propose a framework of social entrepreneurship which can be applied by interested parties. A qualitative phenomenological method research design was employed, which involved two main sources of data: in-depth interviews and reports from social entrepreneurship organisations. Based on purposive sampling techniques, the in-depth interviews were completed involving a total of 19 participants from social entrepreneur, government agencies, NPOs and academics. The study used ATLAS.Ti software application to analyse and interpret data collected from semi-structured interviews. The results discovered that, the social entrepreneurship sector in Malaysia is still in an infancy stage, but it is thriving. The major characteristics of social entrepreneurship found within the samples were related to business viability and impact driven. Based on the findings, challenging elements were found within the participants, namely, challenges posed by internal environments and those by external environments. The results are significant to contribute a comprehensive social entrepreneurship framework development of social entrepreneurship in Malaysia. This framework serves as a substantial tool for the entrepreneurship policy makers to explore the impact of social entrepreneurship activities and to provide opportunities for social entrepreneurship explorations of entrepreneurial activities which have positive impacts on the socioeconomic development in Malaysia.